If the sum of p terms of an
a. P. Is q and the sum of q terms is p, then the sum of p + q terms is ______.
Answers
Answered by
4
Answer:
your answer will be zero.
if you like it then please mark me as a brand list
Answered by
5
Answer:
-(p+q)
let the first term be A and common difference be B
so p th term =a+(p-1)d)and
sum of the first P terms = p/2(2a+(p-1)d)=qhence(2a+(p-1)d)=2q/p......(1)
and q th term =a+(q-1)p
and the sum of the first q terms =q/2(2a+(p-1)d)=p
hence(2a+(qh1)d)=2q/q.....(2)
Subtract (1) from(2)
(p-q)d=2(q/p-p/q)=2(q square - p square)/q
so,d= - 2(p+al/pq)......(3)(p+q)th term =(a+(p+q-1)d)
and sum of its first (p+q)term =(p+q)/2(2a+(p+q-1)d)
now, from (3) , we get,
(2q/p-2-2q/p)×p+q/2
= -(p+q)
THANK YOU FOR THIS QUESTION
PLZ LIKE AND RATE
Similar questions
English,
6 months ago
Math,
6 months ago
Computer Science,
1 year ago
Computer Science,
1 year ago
Math,
1 year ago
Physics,
1 year ago